Neighborhood Effects, Peer Classification, and the Decision of Women to Work - Nuno Mota; Eleonora Patacchini; Stuart S. Rosenthal (Institute for the Study of Labor (IZA), 2016)
We examine the influence of neighborhood peer effects on the decision of women to work using panel data that follows clusters of adjacent homes between 1985-1993. Modeling assumptions imply rank order restrictions that enable us to classify individuals into peer groups while identifying peer effects and underlying mechanisms. For women, peer effects influence labor supply in part because women appear to emulate the work behavior of nearby women with similar age children. For men, peer effects are mostly absent, consistent with inelastic work decisions. Geographically concentrated panel data are crucial for these estimates. Our approach could also be applied to other instances in which neighborhood peer effects are important.
Keywords: R2; J2; 330; neighborhood peer effects; female labor supply